Evaluasi User Experience (UX) Pada Tampilan Website LMS Di UMBS Menggunakan Metode User Experience Questionnaire (UEQ) - Hidayatur Rakhmawati; Rara Yuraiza Arianti; Muhammad Shofi Mahardika; Miftakhu Khoerun (Riset Sinergi Indonesia (RISINDO), 2026)
User experience (UX) refers to the overall experience felt by users before, during, and after interacting with a system or service, encompassing aspects of attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. One standardized instrument widely used to measure UX is the User Experience Questionnaire (UEQ). This study aims to evaluate the UX of the Learning Management System (LMS) website display at Universitas Muhammadiyah Brebes (UMBS) using the UEQ method. The dataset consists of 80 active students of UMBS as respondents. The results showed that all 26 questionnaire items were valid and reliable with Cronbach's Alpha values ranging from 0.857 to 0.898. The UEQ analysis results indicate that the dimensions of perspicuity, efficiency, and dependability fall into the Good category, while attractiveness, stimulation, and novelty fall into the Above Average category, suggesting that the UMBS LMS display already has a fairly good level of user experience, although improvements are still needed particularly in the novelty and attractiveness dimensions.